Does SWPBIS Increase Teachers’ Collective Efficacy? Evidence From a Quasi-experiment - Deltour, Caroline; Dachet, Dylan; Monseur, Christian; Baye, Ariane (Frontiers in Education, 2021)
Teachers’ collective efficacy is predictive of students’ success. School-Wide Positive Behavior Interventions and Supports implementation requires the whole team to set itself common goals regarding behavior management. The main purpose of this study was to investigate the medium-term effects of a SWPBIS intervention on teachers’ collective efficacy. Nine schools and 139 teachers and staff members (n intervention = 74, n control = 65) took part in the study. The study shows that SWPBIS implementation has a positive effect on teachers’ collective efficacy both for primary and secondary schools at post-test 1 (ES = +0.80) and 2 (ES = +0.71). Differences are observed at baseline and at posttests according to the educational level. The link between subscales of a school climate instrument and teachers’ collective efficacy is also investigated. The “structure for learning” subscale explains the greatest variance in collective efficacy.